Chemical Characterisation And The Effect Of Alkaline Pulping Of Malaysia Cultivated Kenaf (Hibiscus Cannabinus) - Ang , Lin Suan (2010)
A comprehensive study is carried out on the chemical composition of the bast and core of the Hibiscus cannabinus (kenaf) cultivated in Malaysia. The changes in the whole stalk chemical composition due to different plant age are also examined. In comparison to the kenaf planted in Malaysia and different countries, the locally planted kenaf (Penang) shows some differences in the value of the chemical composition. Increase of plant age from 15 to 19 weeks of kenaf growth are positively decreases the extractive content, but negatively increases the lignin content and decreases the holocellulose content.